Effects of Supplementation of Zinc, Manganese, or Copper and Different Phytase Levels in Serum and Bone Acid and Alkaline Phosphatases of Broiler Chicks - Santos, L. F.J. [UNESP] (2023)
The knowledge of biological trace minerals and phytase requirements for modern broiler genotypes is not established and the pressure to reduce their usage in animal feeding due to environmental issues is increasing. Here, the alkaline phosphatase (ALP) and tartarate-resistant acid phosphatase (TRAP) of the tibia and serum of broilers fed with diets containing various levels of phytase and reduced levels of zinc, manganese, and copper was evaluated. The experiment was performed using 1,200 male Cobb broilers raised according to standard commercial husbandry techniques. Data were analyzed as a 4×3 factorial arrangement with four concentrations of zinc (0.34, 0.49, 0.64, and 0.79 ppm), manganese (0.18, 0.43, 0.68, and 0.93 ppm), or copper (0.09, 0.12, 0.15, and 0.18 ppm) and three concentrations of phytase (0, 500, and 1,000 FTU/kg) for age periods of 1-21 and 36-42 days. While the dietary supplementation with copper did not induce a significant effect in bone tissue biochemical markers, serum TRAP activity of 42-day old broilers increased with higher copper levels. Increasing dietary zinc levels linearly increased ALP activity in tibia growth, suggesting that zinc is essential for longitudinal bone growth. Phytase significantly promoted the increase of TRAP and ALP activities, suggesting that manganese increased growth plate activity, accelerated calcification, and remodeled the newly formed tissue into trabecular bone. Although not every enzymatic activity was affected by the treatments, the phytase use, along with trace minerals, improved the animal response to the rapid growth required nowadays and provided the nutrients for adequate bone metabolism.